La atención educativa a la diversidad intercultural en los contenidos curriculares de la carrera de ingeniería en tecnologías de la información, de la facultad de ciencias informáticas de la ULEAM - Delgado Reyes, Kléver Alfredo (2017)
The present research work: "The attention to intercultural diversity in the curricular contents of the degree in Information Technology Engineering – IT, of the Faculty of Computer Sciences of the ULEAM, from November 2016 to April 2017", was focuses on an aspect so fundamental for the coexistence of the inhabitants of a nation, as it is the axis of equality of interculturality. The axis of equality of interculturality has had a leading role in the academic world, and all the universities agree on the fundamental thing that is the promotion of the transformation of the Institutions of Higher Education, with a sense of pertinence, inclusion and equity; For this they have redimensioned their educational model, to satisfy the social demand………..